Structural Model of Predicting Marital Satisfaction Based on Attachment Styles and Life Orientation in Married Women: With the Mediating Role of Sensation Seeking - Saboonchi , Faranak; Dokanehi Fard , Farideh; Behboodi , Maasuomeh (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to design a structural model for predicting marital satisfaction based on attachment styles and life orientation with the mediating role of sensation seeking in married women. Method: It is a correlational research and the statistical population was 1854 married women referring to health centers in the north of Tehran in 2018. Using random sampling, Azgol, Araj, Niavaran, and Bagh Ferdows neighborhoods were selected, and from these neighborhoods based on Sample Power software, 350 women were selected. Then, Enrich’s (1989) Marital Satisfaction Questionnaire, Collins and Reed’s Adult Attachment Questionnaire (1990), Shearer and Carver’s (1985) Life Orientation, and Zuckerman’s (1978) Sensation Seeking Questionnaire were completed and the data were analyzed using Smart Plus structural equations. Results: The results showed that the direct path of model fit of secure (β= 0.62), anxious (β= -0.65), and avoidant (β = -0.43) attachment style, life orientation optimistic perception (β = 0.46) and pessimistic perception (β = -0.57) and sensation seeking (β= 0.59) have a positive effect on marital satisfaction. Structural model can also predicate marital satisfaction based on secure (β = 0.53), anxious (β= -0.65), and avoidant (β= -0.43) attachment style, optimistic perception (β= 0.42) and pessimistic perception (β= -0.45) through sensation seeking mediation. Conclusion: The results show that the design of an appropriate structural model for predicting marital satisfaction based on attachment styles and life orientation with the mediating role of sensation seeking is consistent with the theoretical model and has a good fit; Therefore, for the cohesion and creation of a desirable marital relationship, it is possible to improve couples’ relationships by recognizing the emotions of each couple, the type of attachment style and the confrontation of their psychological elements.